Group-target Tracking - Geng, Wen-dong.; Wang, Yuan-qin.; Dong, Zheng-hong.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book describes grouping detection and initiation; group initiation algorithm based on geometry center; data association and track continuity; as well as separate-detection and situation cognition for group-target. It specifies the tracking of the target in different quantities and densities. At the same time, it integrates cognition into the application. Group-target Tracking is designed as a book for advanced-level students and researchers in the area of radar systems, information fusion of multi-sensors and electronic countermeasures. It is also a valuable reference resource for professionals working in this field.
Introduction -- Preliminaries -- Group-target Splitting Detection and Group Initiation -- Single-group-target Data Association and Track Maintenance -- Multi-group-target Data Association and Track Maintenance -- Detection of Group Target Combination and Splitting and Situation Cognition -- Simulations of Group-target Tracking Algorithms.
Keywords: Signal processing; Electronics; Data protection; Algorithms; Signal, Speech and Image Processing .; Electronics and Microelectronics, Instrumentation; Data and Information Security; Algorithms